Current Harmonics Reduction Of Non-Linear Load By Using An Optimal Controller For Active Power Filter - Thajeel, Ekhlas Mhawi; Hamdan, Daniyal; M. H., Sulaiman; Mazin Mustafa, Mahdi (2015)
The increase of the harmonics disturbance in the ac mains currents has become a major concern due to the wide spread of power electronics equipment in modern electrical systems. This paper presents the analysis and simulation of a three-phase active power filter (APF) compensating the harmonics and reactive power created by nonlinear in steady state and in transients using Matlab Simulink. An optimal control strategy for shunt active filter which is proposed in this paper, based on voltage source inverter using Modified Synchronous reference frame theory (SRF) and sinusoidal pulse width modulation (SPWM) Control. The target of this strategy is to improve the behavior of source current when it is crossing from zero. It is seen that the APF has effectively mitigate the Total Harmonic Distortion (THD). The FFT analysis of the active filter system brings the THD of the source current less than 5% into compliance with IEEE-519 harmonic standards.